Colonial Loyalties : Celebrating the Spanish Monarchy in Eighteenth-Century Lima - Barbón, María Soledad (Book collections on Project MUSE., 2019)
"Colonial Loyalties is an insightful study of how Lima's residents engaged in civic festivities in the eighteenth century. Scholarship on festive culture in colonial Latin America has largely centered on "fiestas" as an ideal medium through which the colonizing Iberians naturalized their power. María Soledad Barbón contends that this perspective addresses only one side of the equation. Barbón relies on unprecedented archival research and a wide range of primary sources, including festival narratives, poetry, plays, speeches, and the official and unofficial records of Lima's city council, to explain the level at which residents and institutions in Lima were invested in these rituals. Colonial Loyalties demonstrates how colonial festivals, in addition to reaffirming the power of the monarch and that of his viceroy, opened up opportunities for his subjects. Civic festivities were a means for the populace to strengthen and renegotiate their relationship with the Crown. They also provided the city's inhabitants with a chance to voice their needs and to define their position within colonial society, reasserting their key position in the Spanish empire with respect to other competing cities in the Americas"--